Nitrogen balance on four grasses of the genus Brachiaria - Loureiro, Maria de Fátima; Boddey, Robert Michael (Pesquisa Agropecuaria Brasileira, 2014)
A N balance study was performed on four species of Brachiaria: B. decumbens, B. humidicola, B. radicans and B. ruziziensis. The plants were grown in ten-litre pots in two different soils (a Dark-Red Latosol and Planosol) amended with 15-N labelled ammonium sulphate. Fertilizer treatments with and without molybdenum (Mo) were also imposed. The plants were harvested five times over a period of 14 months and there were no significant differences in the total N accumulation in the aerial tissue of the different grasses over all five harvests, although B. humidicola accumulated more N in the roots than the other species. The total N balances (total final N in soil + N in plant material - total initial N in soil and fertilizer) of all four species grown in the Planosol were positive, although not significantly. The 15-N enrichment of the roots of B. humidicola was significantly lower than that of the other species, indicating a possible input of biologically fixed N to the roots of these species. The percentage values for the recovery of fertilizer in the Planosol (N - fertilizer in soil + N fertilizer recovered by plant) were: 49.5, 53.0, 56.6 and 58.0 for B. radicans, B.decumbens, B. humidicola and B. ruziziensis, respectively. In unplanted pots over 90% of the labelled fertilizer was lost in the Planosol, which demonstrated the importance of the presence of the plants in the retention of N in the soil.